Development of digital learning media based on augmented reality to improve student learning outcomes of elementary school - Nanda Lailatul Nafis; Moh. Fathurrahman (Universitas Muhammadiyah Malang, 2024)
Based on observations that have been made at SDN Agungmulyo, there are problems with student learning outcomes, one of which is monotonous learning. The purpose of this study was to develop and see the effect of using Augmented Reality media on student learning outcomes. The type of research in this study is Research and Development (RnD) research that uses the ADDIE research model with the stages of analysis, design, development, implementation, evaluation. The development of Augmented Reality digital-based learning media products in IPAS subjects is considered valid with an average value from experts of 88%. The results showed an increase in student learning outcomes in grade V IPAS subjects there was an increase of 0.8000 with High criteria on a small scale, and an average increase of 0.5384 with Moderate criteria on a large scale, by the N Gain Test which shows an increase in the average before and after implementing learning, then digital Augmented Reality-based learning media can improve student learning outcomes in IPAS Class V subjects at SDN Agungmulyo Pati. Researchers suggest that education in Indonesia is increasingly able to develop application-based learning media for the advancement of education.